Effect of Feed Withdrawal on Growth Performance and Carcass Characteristics of Heat Stressed Broiler Chicken - Abaseid, Mahasin A.; El Beeli, Sayda A.M. Ali, Mohamed Y.M.; Abdalla, Hyder O. (University of Khartoum Journal of Agricultural Sciences, 2023)
An experiment was conducted to study the effect of feed withdrawal at different ages during the hottest summer days on the growth performance and some carcass traits of broiler chicken. One hundred thirty five male chicks at 14 days of age (DOA) with average body weight (375 g/bird) were randomly allotted to three treatments with three replicates each. The treatments consisted of the control (no feed withdrawal), early feed withdrawal (EFW) at the fourth week of age and late feed withdrawal (LFW) at the fifth week of age. The treatments were assigned to a completely randomized design. The experiment lasted for five weeks having one week as a transitional period, and it was terminated at 49 DOA. The feed withdrawal duration was two weeks for each group. Feed withdrawal was undertaken from 10:00 am till 7:00 pm. Feed intake and live body weight were recorded weekly. Feed conversion ratio (FCR) and the cumulative mortality rate were calculated. Some physical and chemical analyses were carried out for some carcass parts (drumstick and thigh). The abdominal fat pad (AFP) was removed and weighed. The LFW group significantly (P ≤ 0.05) consumed the highest amount of feed, whereas the EFW group consumed the least amount. The cumulative mortality rate was significantly (P ≤ 0.05) lower for LFW and EFW, and the control group recorded the highest rate. At 49 DOA, live body weight was significantly (P ≤ 0.05) the highest for the LFW group, whereas the other groups recorded similar body weights. The overall FCR was significantly (P ≤ 0.05) the best for LFW group, whereas the control had